Предмет: Математика,
автор: Аноним
-5(c+2)-(2c-3)
Якщо с = 1,5
-2(2x-y-3)-2(2x-y)
2(-3a+5b)-4(2a-4b)
Ответы
Автор ответа:
1
-5(с+2)-(2с-3)=-5с-10-2с+3=-7с-7=-7*1,5-7=-10,5-7=-17,5
-2(2х-у-3)-2(2х-у)=-4х+2у+6-4х+2у=-8х+4у+6=-2(4х-2у-3)
2(-3а+5b)-4(2a-4b)=-6a+10b-8a+16b=-14a+26b=-2(7a-13b)
-2(2х-у-3)-2(2х-у)=-4х+2у+6-4х+2у=-8х+4у+6=-2(4х-2у-3)
2(-3а+5b)-4(2a-4b)=-6a+10b-8a+16b=-14a+26b=-2(7a-13b)
Похожие вопросы
Предмет: Литература,
автор: Тёма153
Предмет: Информатика,
автор: Сашуля143
Предмет: Физика,
автор: viks20
Предмет: Физика,
автор: sonia1218
Предмет: Математика,
автор: ruki8